ANALYSIS OF HEAVY METAL CONTENT Pb CuZn IN SEAGRASS (Enhalus acoroides) IN THE COASTAL WATERS OF TANJUNG MEDANG, NORTH RUPATBENGKALIS, RIAU PROVINCE - Fadli Aulia; Yusni Ikhwan Siregar; Bintal Amin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTCoastal water of Tanjung Medang located Northen part of Rupat Island adjacent to Mallacca straits, where anthrophogenic activities increased lately, including marine transport, harbour, settle wents and others. Above activities would lead to pollution coastal water where seagrass (Enhalus acoroides) inhabit. Heavy metals Pb, Cu and Zn were analized fromlocal seagrass which used as bioindicator of pollution. The results showed that the average content of heavy metalsPb in the root, stem and leaf at each station ranged from 1,7556 µg/g - 3,9818 µg/g, and the heavy Cu ranged from 1,0711 µg/g - 1,8499 µg/g, while Zn range for 23,6978 µg/g - 41,7911 µg/g. Mean while heavy metals for the sea water content of Pb ranged from 1,2120 µg/g - 1,8200 µg/g, Cu is 0,5240 µg/g - 1,4693µg/g and Zn is 3,6800 µg/g - 13,7467 µg/g. Plant uptake of heavy metals Pb, Cu and Zn was highest in the roots and leaf. The corelation heavy metals in water and seagrass appeared low. The results suggest that Enhalus acoroides can be used as bio-indicators to describe the condition of the waters of Tanjung Medang contaminated by heavy metals.Key words : Heavy Metals, Enhalus acoroides, Tanjung Medang